2015
DOI: 10.1111/acem.12720
|View full text |Cite
|
Sign up to set email alerts
|

National Cost Savings From Observation Unit Management of Syncope

Abstract: Objectives: Syncope is a frequent emergency department (ED) presenting complaint and results in a disproportionate rate of hospitalization with variable management strategies. The objective was to estimate the annual national cost savings, reduction in inpatient hospitalizations, and reduction in hospital bed hours from implementation of protocolized care in an observation unit.Methods: We created a Monte Carlo simulation by building a model that reflects current clinical practice in the United States and uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…These studies have all favored OU care with improved outcomes such as decrease in diagnostic uncertainty, lower inpatient admission rates, lower cost and length of stay, improved patient satisfaction and quality of life, as well as comparable or better clinical outcomes. In addition, there is a growing body of health services data that illustrates the potential impacts of avoided inpatient admissions and reductions on overall health care cost …”
Section: Definitions and Explanation Of Termsmentioning
confidence: 99%
“…These studies have all favored OU care with improved outcomes such as decrease in diagnostic uncertainty, lower inpatient admission rates, lower cost and length of stay, improved patient satisfaction and quality of life, as well as comparable or better clinical outcomes. In addition, there is a growing body of health services data that illustrates the potential impacts of avoided inpatient admissions and reductions on overall health care cost …”
Section: Definitions and Explanation Of Termsmentioning
confidence: 99%
“…(1) Decreasing these low-yield hospital admissions, or using observation unit syncope protocols, could result in substantial costs savings. (10)…”
Section: Introductionmentioning
confidence: 99%
“…1 Observation units provide clinicians additional time to either provide care or order diagnostic testing that can direct further patient management. 8 EDOUs have been shown to reduce overall hospital costs, 5 , 9 and it is estimated that they may save more than $3.0 billion annually in the U.S. 10 Baugh et al found that using protocols in EDOUs for patients who present with syncope could save more than $100 million annually at a national level. 5 Although it is estimated that only one-third of EDs in the U. S. have an EDOU, 6 – 7 the ratio of EDOU stays to inpatient admissions has been rising.…”
Section: Introductionmentioning
confidence: 99%